Numerical Analysis of Fluid Field & Thermal Field inside Large Wind-generator - 江有名; 丁树业; 葛云中 (Kongzhi Yu Xinxi Jishu)
According to the structure characteristics of large wind generator, a fluid-solid direct coupled model within the whole domain of the generator is established to solve the temperature field of stator and rotor, which based on the fundamental theories of computational fluid dynamics (CFD) and heat transfer theory. Fluid field and temperature field are solved numerically using finite volume method (FVM) by the given conditions. They are also analyzed in detail. Therefore, distribution characters of fluid and temperature inside the generator is obtained, which provide a theory basis for design and operation of this type wind generator.